On the significant impact of the 17 March 2015 St. Patrick's Day geomagnetic storm on the ionosphere over Indian region. Issue 11 (1st December 2022) - Mridula, N.; Manju, G.; Sijikumar, S.; Kumar Pant, Tarun; Kumar Choudhary, Raj
Abstract: The response of the ionosphere in the Indian region to the extreme space weather events of 17–19 March 2015 is studied using Global Positioning System (GPS) Total electron Content (TEC) measurements, Thermosphere Ionosphere Electrodynamics-General Circulation Model (TIE-GCM) simulations and High Frequency (HF) Radar observations. The data from Thiruvananthapuram (8.5° N, 77° E geographic, 0.3° N magnetic latitude) and northern hemispheric midlatitude station Hanle (32.80° N, 79° E geographic, 23.9° N magnetic latitude) have been analyzed for the above event. The TEC over Thiruvananthapuram, a dip equatorial location exhibits a decrease during the post sunset hours on 17 March 2015 and is followed by the generation of F region irregularities at an altitude of 600 km, as observed by HF radar as well as TEC scintillations. The TEC over the mid latitude station of Hanle decreased during the storm recovery phase on 18March 2015 in response to negative storm effects. The extent of decrease in TEC as observed during the recovery phase could not be simulated by TIE-GCM over Hanle. This difference is attributed to the enhanced Joule heating taking place in the polar region during St. Patrick's Day storm and the associated composition changes. An anomalous heating scenario was introduced and the simulated TIE-GCM results were found to match the observations. The present study clearly brings out the impact of 17 March 2015, St. Patrick's Day geomagnetic storm on the ionization distribution over equatorial as well as mid latitude stations over the Indian region using observations as well as TIE-GCM simulations and the evolutionary features of ionospheric irregularities over equatorial location using TEC and HF radar observations. The role played by thermosphere ionosphere coupling in modulating the ionization variability over equatorial as well as mid latitude region during periods of extreme geomagnetic forcing is highlighted.